The potential of soil organic carbon sequestration for climate change mitigation and food security - Frank, Stefan; Havlík, Petr; Soussana, Jean-Francois; Wollenberg, Eva Karoline; Obersteiner, Michael (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Soil organic carbon (SOC) sequestration on agricultural land decreases the costs of climate change mitigation while promoting increased food security. SOC has the potential to sequester up to 3.5 GtCO2eq/yr by 2050 in a scenario consistent with 1.5 ºC warming. In total, the SOC sequestration potential in 2050 could offset around 7% of total emissions in 2010 (IPCC, 2014). SOC sequestration would occur mainly through improved cropland and grassland management, but restoration of organic soils and degraded lands is also significant. SOC sequestration could reduce the negative food security impacts of a carbon tax of 190 $/tCO2eq by as much as 65%, compared to a scenario without SOC sequestration. Under a carbon price policy, farmers would generate revenue from providing SOC sequestration. Hence, farmers contributing SOC sequestration would remain competitive producers in a high carbon price context.